2016
DOI: 10.3390/rs8070572
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Indices Accurately Quantify Changes in Seedling Physiology Following Fire: Towards Mechanistic Assessments of Post-Fire Carbon Cycling

Abstract: Fire activity, in terms of intensity, frequency, and total area burned, is expected to increase with a changing climate. A challenge for landscape-level assessment of fire effects, often termed burn severity, is that current remote sensing assessments provide very little information regarding tree/vegetation physiological performance and recovery, limiting our understanding of fire effects on ecosystem services such as carbon storage/cycling. In this paper, we evaluated whether spectral indices common in veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
66
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 58 publications
(60 reference statements)
5
66
1
Order By: Relevance
“…While this approach is widely used and accepted as a proxy for holistic fire effects, the empirical links between spectral indices and biometric measures of fire intensity and effects are still quite limited and lacking robust ecological connections and applications (Lentile et al 2006, Kolden et al 2015b, particularly because there is rarely pre-fire biometric or field data from which to assess relative change. Recent efforts to quantify relationships between fire energy released and physiological tree responses have demonstrated the utility of an alternative framework (Smith et al 2016b, Sparks et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…While this approach is widely used and accepted as a proxy for holistic fire effects, the empirical links between spectral indices and biometric measures of fire intensity and effects are still quite limited and lacking robust ecological connections and applications (Lentile et al 2006, Kolden et al 2015b, particularly because there is rarely pre-fire biometric or field data from which to assess relative change. Recent efforts to quantify relationships between fire energy released and physiological tree responses have demonstrated the utility of an alternative framework (Smith et al 2016b, Sparks et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Under controlled experiments on saplings, a toxicological "dose-response" relationship was observed, whereby increasing FRE resulted in decreasing net photosynthesis in surviving Pinus contorta and Larix occidentalis saplings and increased mortality 1 year post-fire . Furthermore, Sparks et al (2017) observed decreasing radial growth in mature Pinus ponderosa 1.5 years post-fire with increasing peak FRP. These findings suggest that there is a strong link between measures of fire intensity and subsequent vegetation productivity and mortality.…”
Section: Introductionmentioning
confidence: 84%
“…Recent studies have observed that increasing fire radiative energy (FRE: J ) and peak fire radiative power (FRP: W ) incident on trees results in reduced tree growth and increased mortality Sparks et al, , 2017. FRP is the instantaneous radiative flux, which is strongly related to common field-based fire intensity metrics (Kaufman et al, 1996;Kremens et al, 2012;Sparks et al, 2017), and its temporal integral is FRE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former provides rich spectrum that can reflect the biochemical information of the target and the latter provides detailed geometric information relating to the structural properties of the object. Both of the two techniques have been widely applied in vegetation physiology [3], precision agriculture [4], radiative transfer modeling [5], etc.…”
Section: Introductionmentioning
confidence: 99%